High-strength aluminum oxide ceramic and processing technology thereof
By using dispersants and inorganic salts and other components, combined with ball milling and sintering processes, the agglomeration and density problems of alumina ceramics during the preparation process are solved, and high-strength and high-density alumina ceramics are achieved, which improves its mechanics performance.
Patent Information
- Application Number
- CN202311574414.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-23
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-11-23
AI Technical Summary
During the preparation process, the existing alumina ceramics are agglomerated and enhanced heterophase deposition between particles, resulting in slurry gel curing and body density limited, affecting the strength and performance of the ceramics.
Dispersants such as Isobam104, Isobam600AF and branched polyamide are used to disperse the alumina particles through ball milling and dehydration processes, graphene and inorganic salts are added to inhibit agglomeration, and high-temperature sintering process is combined to form a high-density alumina ceramic.
The high strength and high density of alumina ceramics are achieved, their mechanical properties and bending strength are improved, and the sintering temperature and porosity are reduced.
Smart Images

Figure BDA0004566572850000091 
Figure BDA0004566572850000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alumina ceramics, in particular to a high-strength alumina ceramic and a processing technology thereof. Background Art
[0002] With the progress of science and technology, the research on ceramic materials has made great progress. Due to its high mechanical strength and excellent high temperature resistance, wear resistance, corrosion resistance, chemical stability and other characteristics, alumina ceramics are widely used in electrical and electronic, automotive, biological, medical, aerospace and other fields. Existing alumina ceramics are usually prepared by pressing and casting processes. Gel injection molding has attracted widespread attention for its ability to prepare large-size, complex-shaped, low-shrinkage, low-cost and high-precision ceramics. The basic molding principle uses organic matter to fix micro-nano-scale alumina particles in situ, bond and solidify them into a green body, and then sinter them into alumina ceramics. However, micro-nano-scale alumina particles are prone to agglomeration, and heterogeneous deposition will also occur between some added reinforcing particles, which will have a negative impact on the gel curing of the slurry and the density of the green body. Therefore, we propose a high-strength alumina ceramic and its processing technology. Summary of the invention
[0003] The object of the present invention is to provide a high-strength alumina ceramic and a processing technology thereof to solve the problems raised in the above background technology.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a high-strength alumina ceramic and a processing technology thereof, comprising the following processes:
[0005] Step 1, dissolving a dispersant in deionized water to obtain a mixed solution; placing the mixed solution and graphene in a ball mill, adding a grinding medium and starting the stirred mill, slowly adding alumina to the stirred mill, and ball milling for 1 to 4 hours to obtain a slurry;
[0006] Step 2: dehydrate the slurry obtained in step 1 under constant temperature and humidity conditions for 1 to 6 days, seal and filter in a filter press mold to obtain a green body;
[0007] Place in a muffle furnace at 800-1000°C for 2-6 hours to remove binder;
[0008] After heating to 1850℃ once, cool down to 1400~1500℃ and keep warm for 2~3h, heat up to 1850℃ for the second time and keep warm for 6h.
[0009] Further, in step 1, the rotation speed of the stirring mill is 200 to 300 r / min;
[0010] The grinding medium is zirconium oxide, and the added amount of the grinding medium is 1.1 to 1.2 times the mass of aluminum oxide.
[0011] Furthermore, in step 2, the constant temperature and humidity conditions are: temperature 25° C., relative humidity 85%;
[0012] The pressure applied in the filter press process is 0.37-0.45 MPa;
[0013] The heating rate in the debinding process is 1-2°C / min;
[0014] The primary heating rate in the sintering process is 10°C / min, and the secondary heating rate is 2°C / min.
[0015] Furthermore, the slurry includes the following components by mass: 100 parts of aluminum oxide, 0.6 to 1.0 parts of graphene, and 0.2 to 0.4 parts of a dispersant.
[0016] Furthermore, the slurry also includes the following components by mass: 13.0 to 13.4 parts of aluminum nitride, 0.34 to 0.40 parts of yttrium oxide, and 0.026 to 0.030 parts of lanthanum oxide.
[0017] Furthermore, the solid content of the slurry is 40-55 vol%.
[0018] Alumina: α-Al2O3 powder, particle size 0.4-0.6 μm, sourced from Beijing Dekedaojin Technology Co., Ltd.;
[0019] Graphene: flake, particle size 0.8-1.2 μm, from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;
[0020] Aluminum nitride: The average particle size is 0.6 μm, sourced from Tianyuan Aerospace Materials (Yingkou) Technology Co., Ltd.
[0021] Yttrium oxide: particle size is 0.8-1.5 μm, sourced from Ganzhou Guangli High-tech Materials Co., Ltd.
[0022] Lanthanum oxide: particle size is 0.8-1.5 μm, sourced from Ganzhou Guangli High-tech Materials Co., Ltd.
[0023] Further, the dispersant is one or more of Isobam104, Isobam600AF, polyammonium acrylate PAA-NH2, and branched polyamide;
[0024] After the ball milling process in step 1 is completed, inorganic salt is added and the ball milling is continued for 50 to 75 minutes;
[0025] The inorganic salt is one of cesium chloride and magnesium chloride, and the concentration of the inorganic salt in the slurry is 120 to 180 ppm.
[0026] Isobam104: average molecular weight 55000-65000; Isobam600AF: average molecular weight 5500-6500, both from Kuraray of Japan; ammonium polyacrylate: from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0027] Further, the branched polyamide is prepared by the following process:
[0028] (1) Mix and dissolve trimesic acid, pyridine, and N-methylpyrrolidone, add triphenyl phosphite, raise the temperature to 100-110° C., slowly add 1,8-octanediamine, add the mixture within 2 hours, and react for 1-3 hours to obtain an amide product;
[0029] (2) The amide product and 2-carboxymethoxy-5-methylbenzenesulfonic acid sodium salt are placed in a reactor, and N-methylpyrrolidone, pyrrole, triphenyl phosphite, calcium chloride, and lithium chloride are added and mixed evenly. Under the protection of a nitrogen atmosphere, the temperature is raised to 105-115° C., and the reaction is stirred for 24 hours; the product is cooled to room temperature, placed in acetone for precipitation, filtered, washed, and dried to obtain a branched polyamide.
[0030] Furthermore, in the step (1), the molar ratio of trimesic acid to 1,8-octanediamine is 1:(3.1-3.3);
[0031] The molar ratio of 1,8-octanediamine and pyridine is 1:1;
[0032] The molar ratio of trimesic acid to triphenyl phosphite is 1:3;
[0033] The ratio of trimesic acid to N-methylpyrrolidone is 0.20-0.22 mol / L.
[0034] Furthermore, in the step (2), the molar ratio of the amide product to 2-carboxymethoxy-5-methylbenzenesulfonic acid sodium salt is 1:(1.0-1.1);
[0035] The ratio of amide product and N-methylpyrrolidone is (20-25) g:100 mL;
[0036] The mass ratio of the amide product, pyrrole, triphenyl phosphite, calcium chloride and lithium chloride is 10:(23.0-23.2):(2.23-2.25):(0.74-0.76).
[0037] In the above technical scheme, when the dispersant is a mixture of Isobam104 and Isobam600AF, it has amide, carboxylate ions and carboxylic acid anhydride, which can be used as a gelling system of ceramic slurry to disperse and gel alumina particles and realize injection molding of alumina. In the slurry material system, the carboxylic acid anhydride in Isobam is hydrolyzed. Since the Zeta potential of nano alumina in a neutral aqueous solution is positive, it can be considered to be positively charged. The carboxylate ions can be adsorbed on the surface positive charge of alumina, so that the surface of alumina is negatively charged, increasing the electrostatic repulsion potential between alumina particles, so that the slurry has good fluidity; and since Isobam has a large molecular weight, the polymer chain is fully extended in the grafting to form an adsorption layer with a thickness of several nanometers to tens of nanometers, producing a steric hindrance effect, and the above electrostatic repulsion can effectively prevent the agglomeration of alumina particles, thereby providing electrostatic and spatial stability for alumina, achieving a dispersion effect, and obtaining a low-viscosity suspension. As the ball milling time increases, the repulsion between the alumina particles disappears. At this time, there is only attraction between the particles. The unadsorbed carboxylate anions bond with the amide in the system to form hydrogen bonds, the alumina particles are bridged and solidified, the viscosity of the slurry increases, and gel solidification occurs, thereby achieving the injection molding of alumina. When the dispersant is ammonium polyacrylate, it has the same technical effects as above. The branched polyamide dispersant in this application has amide and sodium sulfonate groups and has the same or similar technical effects as above.
[0038] The non-metallic compound graphene is also added to the slurry component of the present application. As the second phase in the alumina ceramic, it can inhibit the growth of the alumina grain structure, play a role in refining the grains, strengthen and toughen the prepared alumina ceramic, and improve its mechanical properties. The amine group in the above dispersant component will modify the graphene, so that the amine group is adsorbed on the surface of the graphene, promoting the dispersion of the graphene in the slurry, while the carboxylate ions embody electrostatic repulsion in the grafting, and no gel curing effect is produced; and in the slurry system, graphene and aluminum nitride will attract alumina, so that graphene and aluminum nitride are adsorbed on the surface of alumina, causing heterogeneous deposition, hindering the gel curing of the slurry; and graphene and aluminum nitride repel each other, which will also cause uneven distribution of the two in the slurry. Therefore, after the dispersant and the powder (alumina, graphene, aluminum nitride, etc.) are ball-milled and mixed, the present application adds a water-soluble metal inorganic salt to introduce the metal ions into the slurry system, and reacts with the negatively charged groups such as carboxylate ions and sulfonate ions in the dispersant through ionic bonds; wherein, as alkali metal elements, magnesium and cesium, through adsorption with carboxylate ions and sulfonate ion bonds, form a self-assembled structure with the dispersant, and form a hexagonal phase with the branched polyamide, which increases the cross-linking between the dispersant molecules, can enhance the anisotropy of the above-mentioned dispersant on the surface of the alumina particles, promote the solidification of the slurry gel, form a three-dimensional network of the gel, improve the gel strength, and contribute to the improvement of the mechanical properties of the prepared alumina ceramics. And the introduction of the metal element magnesium / the replacement of the metal sodium element with the metal element cesium contributes to the diffusion of the grain boundaries of the alumina ceramics, promotes the discharge of pores, and improves the density and strength of the prepared alumina ceramics.
[0039] Through the reaction between the components of trimesic acid, 1,8-octanediamine, and 2-carboxymethoxy-5-methylbenzenesulfonic acid sodium salt, a small molecule polyamide with a symmetrical structure centered on trimesic acid and sodium sulfonate as the end group was obtained, namely branched polyamide. After reacting with inorganic salts, the surface charge in the above-mentioned self-assembled structure was changed, which can make alumina condense around the self-assembled structure, promote the dispersion and aggregation of powder particles such as alumina in the green body, and improve the dispersibility of the slurry system while improving the density of the green body and the prepared alumina ceramics. At the same time, the molecular weight of the branched polyamide is small, the steric hindrance is weakened, and the difficulty of debinding is reduced, which helps to further improve the mechanical properties of its alumina ceramics.
[0040] Then, filter pressing and dehydration shrinkage are carried out. The grading effect between the powder particles makes the slurry have a certain compressibility, so that the free water in the slurry is discharged, and the solid content of the slurry is increased to a certain extent, thereby obtaining a green body with a higher density, which helps to improve the mechanical properties of alumina ceramics.
[0041] Finally, sintering is carried out, and yttrium oxide and lanthanum oxide are compounded as sintering aids and distributed on the surface of alumina particles. A low melting point liquid phase is formed, and the pores between the powder particles are filled through the capillary action between the powder particles, thereby reducing the porosity of the prepared alumina ceramic, increasing the density and reducing the sintering temperature. During the sintering process, the sintering temperature is first raised to 1850°C so that the green body reaches above the critical density, and then kept at a lower temperature. At this time, the pores in the green body gradually shrink through grain boundary diffusion, making it gradually densified; because the activation energy of grain boundary diffusion is lower than the activation energy of grain boundary migration, the grains grow mainly through grain boundary migration, and are pinned by the pores, and the grain structure remains the original size and does not change. The secondary heating and heat preservation further eliminates the residual pores in the green body, weakens the pinning effect of the pores, promotes the growth of grains due to grain boundary migration, further eliminates the pores, and improves the relative density of the ceramic. Graphene is deposited between the alumina grains, which can inhibit the growth of alumina grains, refine the grains, strengthen and toughen the alumina ceramics, and thus improve the mechanical properties of the alumina ceramics.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] The high-strength alumina ceramics and the processing technology thereof of the present invention, by adjusting the process and the required alumina ceramic preparation components, coordinate the dispersant with the inorganic salt and the process, promote the gel solidification of the slurry and improve the density of the green body, thereby obtaining alumina ceramics with high strength. DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] In the following specific embodiments, alumina: α-Al2O3 powder, with a particle size of 0.4-0.6 μm, is sourced from Beijing Dekedaojin Technology Co., Ltd.;
[0046] Graphene: flake, particle size 0.8-1.2 μm, from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;
[0047] Aluminum nitride: The average particle size is 0.6 μm, sourced from Tianyuan Aerospace Materials (Yingkou) Technology Co., Ltd.
[0048] Yttrium oxide: particle size is 0.8-1.5 μm, sourced from Ganzhou Guangli High-tech Materials Co., Ltd.
[0049] Lanthanum oxide: particle size is 0.8-1.5 μm, sourced from Ganzhou Guangli High-tech Materials Co., Ltd.
[0050] Isobam104: average molecular weight 55000-65000; Isobam600AF: average molecular weight 5500-6500, both from Japan Kuraray;
[0051] Ammonium polyacrylate: Sourced from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0052] The number of "portions" here is 10 grams.
[0053] Embodiment 1: A high-strength alumina ceramic and a processing technology thereof, comprising the following processes:
[0054] Step 1, dissolving 0.1 parts of Isobam104 and 0.2 parts of Isobam600AF in deionized water to obtain a mixed solution; placing the mixed solution and 0.6 parts of graphene in a ball mill, adding 110 parts of grinding medium zirconium oxide, and starting the stirred mill at a speed of 200r / min, slowly adding 100 parts of aluminum oxide, 13.0 parts of aluminum nitride, 0.34 parts of yttrium oxide, and 0.026 parts of lanthanum oxide to the stirred mill, and ball milling for 1h; adding inorganic salt magnesium chloride, and continuing ball milling for 50min; obtaining a slurry with a solid content of 40vol%; the concentration of magnesium chloride in the slurry is 120ppm;
[0055] Step 2: Dehydrate the slurry obtained in step 1 under constant temperature and humidity conditions of 25°C and 85% relative humidity for 1 day, seal it in a filter press mold and apply a pressure of 0.37 MPa to obtain a green body; place it in a muffle furnace, heat it to 1000°C at a heating rate of 1°C / min, and keep it warm for 6 hours to remove binder; heat it to 1850°C at a heating rate of 10°C / min, then cool it to 1500°C, keep it warm for 2 hours, heat it to 1850°C at a heating rate of 2°C / min, and keep it warm for 6 hours.
[0056] Embodiment 2: A high-strength alumina ceramic and a processing technology thereof, comprising the following processes:
[0057] Step 1, dissolving 0.35 parts of ammonium polyacrylate in deionized water to obtain a mixed solution; placing the mixed solution and 0.8 parts of graphene in a ball mill, adding 110 parts of grinding medium zirconium oxide, and starting the stirred mill, the speed of the stirred mill is 250r / min, slowly adding 100 parts of aluminum oxide, 13.2 parts of aluminum nitride, 0.37 parts of yttrium oxide, and 0.028 parts of lanthanum oxide to the stirred mill, and ball milling for 2.5h; adding inorganic salt magnesium chloride, and continuing ball milling for 60min; obtaining a slurry with a solid content of 47vol%; the concentration of magnesium chloride in the slurry is 180ppm;
[0058] Step 2: Dehydrate the slurry obtained in step 1 under constant temperature and humidity conditions of 25°C and 85% relative humidity for 3 days, seal it in a filter press mold and apply a pressure of 0.40 MPa to obtain a green body; place it in a muffle furnace, heat it to 900°C at a heating rate of 2°C / min, and keep it warm for 4 hours to remove binder; heat it to 1850°C at a heating rate of 10°C / min, then cool it to 1450°C, keep it warm for 3 hours, heat it to 1850°C at a heating rate of 2°C / min, and keep it warm for 6 hours.
[0059] Embodiment 3: A high-strength alumina ceramic and a processing technology thereof, comprising the following processes:
[0060] Preparation of branched polyamide:
[0061] Take 2.5g of trimesic acid, 0.8g of pyridine, and 50mL of N-methylpyrrolidone, mix and dissolve, add 9.3g of triphenyl phosphite, heat to 100°C, slowly add 4.4g of 1,8-octanediamine, add within 2h, react for 1h, and obtain an amide product;
[0062] 10 g of the amide product and 7.8 g of 2-carboxymethoxy-5-methylbenzenesulfonic acid sodium salt were placed in a reactor, 50 mL of N-methylpyrrolidone, 8.3 mL of pyrrole, 23.0 g of triphenyl phosphite, 2.23 g of calcium chloride, and 0.74 g of lithium chloride were added, and mixed evenly. Under the protection of a nitrogen atmosphere, the temperature was raised to 105° C., and the reaction was stirred for 24 h; the mixture was cooled to room temperature, precipitated in acetone, filtered, washed, and dried to obtain a branched polyamide;
[0063] Step 1, dissolving 0.30 parts of branched polyamide in deionized water to obtain a mixed solution; placing the mixed solution and 1.0 parts of graphene in a ball mill, adding 120 parts of grinding medium zirconium oxide, and starting the stirred mill, the speed of the stirred mill is 250r / min, slowly adding 100 parts of aluminum oxide, 13.4 parts of aluminum nitride, 0.4 parts of yttrium oxide, and 0.03 parts of lanthanum oxide to the stirred mill, and ball milling for 4h; adding inorganic salt cesium chloride, and continuing ball milling for 75min; obtaining a slurry with a solid content of 55vol%; the concentration of magnesium chloride in the slurry is 150ppm;
[0064] Step 2: Dehydrate the slurry obtained in step 1 under constant temperature and humidity conditions of 25°C and 85% relative humidity for 3 days, seal it in a filter press mold and apply a pressure of 0.45 MPa to obtain a green body; place it in a muffle furnace, heat it to 800°C at a heating rate of 2°C / min, and keep it warm for 6 hours to remove binder; heat it to 1850°C at a heating rate of 10°C / min, then cool it to 1400°C, keep it warm for 3 hours, heat it to 1850°C at a heating rate of 2°C / min, and keep it warm for 6 hours.
[0065] Embodiment 4: A high-strength alumina ceramic and a processing technology thereof, comprising the following processes:
[0066] Preparation of branched polyamide:
[0067] Take 2.5g of trimesic acid, 0.8g of pyridine, and 50mL of N-methylpyrrolidone, mix and dissolve, add 9.3g of triphenyl phosphite, heat to 105°C, slowly add 4.5g of 1,8-octanediamine, add within 2h, react for 2h, and obtain an amide product;
[0068] 10 g of the amide product and 8.2 g of 2-carboxymethoxy-5-methylbenzenesulfonic acid sodium salt were placed in a reactor, and 50 mL of N-methylpyrrolidone, 8.3 mL of pyrrole, 23.1 g of triphenyl phosphite, 2.24 g of calcium chloride, and 0.75 g of lithium chloride were added, mixed evenly, heated to 110° C. under nitrogen atmosphere protection, and stirred for reaction for 24 h; cooled to room temperature, placed in acetone for precipitation, filtered, washed, and dried to obtain a branched polyamide;
[0069] Step 1, dissolving 0.35 parts of branched polyamide in deionized water to obtain a mixed solution; placing the mixed solution and 1.0 parts of graphene in a ball mill, adding 120 parts of grinding medium zirconium oxide, and starting the stirred mill, the speed of the stirred mill is 250r / min, slowly adding 100 parts of aluminum oxide, 13.4 parts of aluminum nitride, 0.4 parts of yttrium oxide, and 0.03 parts of lanthanum oxide to the stirred mill, and ball milling for 4h; adding inorganic salt cesium chloride, and continuing ball milling for 75min; obtaining a slurry with a solid content of 55vol%; the concentration of magnesium chloride in the slurry is 150ppm;
[0070] Step 2: Dehydrate the slurry obtained in step 1 under constant temperature and humidity conditions of 25°C and 85% relative humidity for 3 days, seal it in a filter press mold and apply a pressure of 0.45 MPa to obtain a green body; place it in a muffle furnace, heat it to 800°C at a heating rate of 2°C / min, and keep it warm for 6 hours to remove binder; heat it to 1850°C at a heating rate of 10°C / min, then cool it to 1400°C, keep it warm for 3 hours, heat it to 1850°C at a heating rate of 2°C / min, and keep it warm for 6 hours.
[0071] Embodiment 5: A high-strength alumina ceramic and a processing technology thereof, comprising the following processes:
[0072] Preparation of branched polyamide:
[0073] Take 2.5g of trimesic acid, 0.8g of pyridine, and 50mL of N-methylpyrrolidone, mix and dissolve, add 9.3g of triphenyl phosphite, heat to 110°C, slowly add 4.7g of 1,8-octanediamine, add within 2h, react for 3h, and obtain an amide product;
[0074] 10 g of the amide product and 8.6 g of 2-carboxymethoxy-5-methylbenzenesulfonic acid sodium salt were placed in a reactor, 50 mL of N-methylpyrrolidone, 8.3 mL of pyrrole, 23.2 g of triphenyl phosphite, 2.25 g of calcium chloride, and 0.76 g of lithium chloride were added, and mixed evenly. Under the protection of a nitrogen atmosphere, the temperature was raised to 105-115° C., and the reaction was stirred for 24 h; the product was cooled to room temperature, precipitated in acetone, filtered, washed, and dried to obtain a branched polyamide;
[0075] Step 1, dissolving 0.40 parts of branched polyamide in deionized water to obtain a mixed solution; placing the mixed solution and 1.0 parts of graphene in a ball mill, adding 120 parts of grinding medium zirconium oxide, and starting the stirred mill, the speed of the stirred mill is 250r / min, slowly adding 100 parts of aluminum oxide, 13.4 parts of aluminum nitride, 0.4 parts of yttrium oxide, and 0.03 parts of lanthanum oxide to the stirred mill, and ball milling for 4h; adding inorganic salt cesium chloride, and continuing ball milling for 75min; obtaining a slurry with a solid content of 55vol%; the concentration of magnesium chloride in the slurry is 150ppm;
[0076] Step 2: Dehydrate the slurry obtained in step 1 under constant temperature and humidity conditions of 25°C and 85% relative humidity for 3 days, seal it in a filter press mold and apply a pressure of 0.45 MPa to obtain a green body; place it in a muffle furnace, heat it to 800°C at a heating rate of 2°C / min, and keep it warm for 6 hours to remove binder; heat it to 1850°C at a heating rate of 10°C / min, then cool it to 1400°C, keep it warm for 3 hours, heat it to 1850°C at a heating rate of 2°C / min, and keep it warm for 6 hours.
[0077] Comparative Example 1: A high-strength alumina ceramic and a processing technology thereof, comprising the following processes:
[0078] Step 1, dissolving 0.1 parts of Isobam104 and 0.2 parts of Isobam600AF in deionized water to obtain a mixed solution; placing the mixed solution and 0.6 parts of graphene in a ball mill, adding 110 parts of grinding medium zirconium oxide, and starting the stirred mill at a speed of 200 r / min, slowly adding 100 parts of aluminum oxide, 13.0 parts of aluminum nitride, 0.34 parts of yttrium oxide, and 0.026 parts of lanthanum oxide to the stirred mill, ball milling for 1 hour, and obtaining a slurry with a solid content of 40 vol%;
[0079] Step 2: Dehydrate the slurry obtained in step 1 under constant temperature and humidity conditions of 25°C and 85% relative humidity for 1 day, seal it in a filter press mold and apply a pressure of 0.37 MPa to obtain a green body; place it in a muffle furnace, heat it to 1000°C at a heating rate of 1°C / min, and keep it warm for 6 hours to remove binder; heat it to 1850°C at a heating rate of 10°C / min, then cool it to 1500°C, keep it warm for 2 hours, heat it to 1850°C at a heating rate of 2°C / min, and keep it warm for 6 hours.
[0080] Comparative Example 2: A high-strength alumina ceramic and a processing technology thereof, comprising the following processes:
[0081] Step 1, dissolving 0.1 parts of Isobam104 and 0.2 parts of Isobam600AF in deionized water to obtain a mixed solution; placing the mixed solution in a ball mill, adding 110 parts of grinding medium zirconium oxide, and starting the stirred mill at a speed of 200 r / min, slowly adding 100 parts of aluminum oxide, 13.0 parts of aluminum nitride, 0.34 parts of yttrium oxide, and 0.026 parts of lanthanum oxide to the stirred mill, ball milling for 1 hour, and obtaining a slurry with a solid content of 40 vol%;
[0082] Step 2: Dehydrate the slurry obtained in step 1 under constant temperature and humidity conditions of 25°C and 85% relative humidity for 1 day, seal it in a filter press mold and apply a pressure of 0.37 MPa to obtain a green body; place it in a muffle furnace, heat it to 1000°C at a heating rate of 1°C / min, and keep it warm for 6 hours to remove binder; heat it to 1850°C at a heating rate of 10°C / min, then cool it to 1500°C, keep it warm for 2 hours, heat it to 1850°C at a heating rate of 2°C / min, and keep it warm for 6 hours.
[0083] Comparative Example 3: A high-strength alumina ceramic and a processing technology thereof, comprising the following processes:
[0084] Step 1, dissolving 0.1 parts of Isobam104 and 0.2 parts of Isobam600AF in deionized water to obtain a mixed solution; placing the mixed solution in a ball mill, adding 110 parts of grinding medium zirconium oxide, and starting the stirred mill at a speed of 200 r / min, slowly adding 113 parts of aluminum oxide, 0.34 parts of yttrium oxide, and 0.026 parts of lanthanum oxide to the stirred mill, ball milling for 1 hour, and obtaining a slurry with a solid content of 40 vol%;
[0085] Step 2: Dehydrate the slurry obtained in step 1 under constant temperature and humidity conditions of 25°C and 85% relative humidity for 1 day to obtain a green body; place it in a muffle furnace, heat it to 1000°C at a heating rate of 1°C / min, and keep it warm for 6 hours to remove binder; heat it to 1850°C at a heating rate of 10°C / min, then cool it to 1500°C, keep it warm for 2 hours, heat it to 1850°C at a heating rate of 2°C / min, and keep it warm for 6 hours.
[0086] experiment
[0087] The alumina ceramics obtained in Examples 1-5 and Comparative Examples 1-3 were used to prepare samples, and their properties were tested and the test results were recorded:
[0088] The three-point bending method was used to test the bending strength of the sample using a bending strength tester. The sample size was 3mm×4mm×35mm.
[0089] The fracture toughness of the specimens was tested using the single-edge notched beam method, with specimen dimensions of 3 mm × 4 mm × 35 mm and a notch size of 2 mm.
[0090] The density of the sample was tested by the Archimedes drainage method, and the relative density of the sample was obtained based on theoretical conversion.
[0091]
[0092]
[0093] According to the data in the above table, we can clearly draw the following conclusions:
[0094] The alumina ceramics obtained in Examples 1-5 are compared with the alumina ceramics obtained in Comparative Examples 1-3. The test results show that:
[0095] Compared with the comparative example, the alumina ceramics obtained in Examples 1-5 have higher flexural strength, fracture toughness and relative density data, which fully demonstrates that the present invention achieves the improvement of the density and mechanical properties of the prepared alumina ceramics.
[0096] Compared with Example 1, the component magnesium chloride is not added in Comparative Example 1; the components magnesium chloride and graphene are not added in Comparative Example 2; the components magnesium chloride, graphene and aluminum nitride are not added in Comparative Example 3; the alumina ceramics obtained in Comparative Examples 1-3 have reduced flexural strength, fracture toughness and relative density data. It can be seen that the setting of the preparation process and the required components of the present invention can promote the improvement of the density and mechanical properties of the prepared alumina ceramics.
[0097] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0098] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A processing technology for high-strength alumina ceramics, characterized in that: Including the following processes: Step 1, dissolving a dispersant in deionized water to obtain a mixed solution; placing the mixed solution and graphene in a ball mill, adding a grinding medium and starting the stirred mill, slowly adding alumina to the stirred mill, and ball milling for 1 to 4 hours to obtain a slurry; Step 2, dehydrating the slurry obtained in step 1 at a temperature of 25° C. and a relative humidity of 85% for 1 to 6 days, sealing and filtering in a filter press mold to obtain a green body; Place in a muffle furnace at 800-1000°C for 2-6 hours to remove binder; After heating to 1850℃ once, cool down to 1400~1500℃ and keep warm for 2~3h, heat up to 1850℃ for the second time and keep warm for 6h.
2. The processing technology of high-strength alumina ceramics according to claim 1, characterized in that: The slurry also includes the following components by mass: 13.0 to 13.4 parts of aluminum nitride, 0.34 to 0.40 parts of yttrium oxide, and 0.026 to 0.030 parts of lanthanum oxide.
3. The processing technology of high-strength alumina ceramics according to claim 1, characterized in that: The slurry also includes the following components by mass: 13.0 to 13.4 parts of aluminum nitride, 0.34 to 0.40 parts of yttrium oxide, and 0.026 to 0.030 parts of lanthanum oxide.
4. The processing technology of high-strength alumina ceramics according to claim 1, characterized in that: The solid content of the slurry is 40-55 vol%.
5. The processing technology of high-strength alumina ceramics according to claim 1, characterized in that: The dispersant is one or more of Isobam104, Isobam600AF, ammonium polyacrylate, and branched polyamide.
6. The processing technology of high-strength alumina ceramics according to claim 1, characterized in that: After the ball milling process in step 1 is completed, inorganic salt is added and the ball milling is continued for 50 to 75 minutes; The inorganic salt is one of cesium chloride and magnesium chloride, and the concentration of the inorganic salt in the slurry is 120 to 180 ppm.
7. The processing technology of high-strength alumina ceramics according to claim 5, characterized in that: The branched polyamide is prepared by the following process: Take trimesic acid, pyridine and N-methylpyrrolidone and dissolve them in a mixture, add triphenyl phosphite, raise the temperature to 100-110°C, slowly add 1,8-octanediamine, add it within 2 hours, react for 1-3 hours, and obtain an amide product; The amide product and 2-carboxymethoxy-5-methylbenzenesulfonic acid sodium salt are placed in a reactor, and N-methylpyrrolidone, pyrrole, triphenyl phosphite, calcium chloride and lithium chloride are added, mixed evenly, heated to 105-115° C. under the protection of a nitrogen atmosphere, and stirred for reaction for 24 hours; cooled to room temperature, placed in acetone for precipitation, filtered, washed and dried to obtain a branched polyamide.
8. The processing technology of high-strength alumina ceramics according to claim 7, characterized in that: The molar ratio of trimesic acid to 1,8-octanediamine is 1:(3.1-3.3).
9. The processing technology of high-strength alumina ceramics according to claim 7, characterized in that: The molar ratio of the amide product to 2-carboxymethoxy-5-methylbenzenesulfonic acid sodium salt is 1:(1.0-1.1).
10. A high-strength alumina ceramic obtained by the processing technology according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of graphene-nanosheet-reinforced alumina ceramic
CN103044014A
Toughened alumina ceramic mobile phone backboard and preparation method thereof
CN108675812A
Aluminum nitride nanoflower / polymer composite material and preparation method thereof
CN113480828A
Anti-static aluminum oxide ceramic material and preparation method thereof
CN113698182A
Manufacturing method of alumina-graphene composites with excellent wear resistance
KR1020170006002A
